Mastery Learning Assessment Model (MLAM) in Teaching and Learning Mathematics - ., Norazzila Shafie, Tengku Norainun Tengku Shahdan, Mohd Shahir Li (2010)
This study examined the effectiveness of Mastery Learning Assessment Model (MLAM) in teaching and learning mathematics at a private university, namely UNIRAZAK, Malaysia. MLAM was based on repeating similar assessments through a mastery learning remodel from previous researchers. In this study presented herein, a sample size of 30 was collected and surveyed using continuous assessments and the findings showed that a positive correlation (r=0.77) exists between the MLAM score and the final exam result. Based on the Teaching Evaluation Results (TER), a majority of the students were also satisfied with this approach.